Early Renal Dysfunction and Reduced Retinal Vascular Density Assessed by Angio-OCT in Hypertensive Patients - Caterina Carollo; Maria Vadalà; Alessandra Sorce; Emanuele Cirafici; Miriam Bennici; Massimo Castellucci; Vincenza Maria Elena Bonfiglio; Giuseppe Mulè; Giulio Geraci (Biomedicines)
Background: The eye and kidney share embryological, structural, and pathophysiological similarities, suggesting potential interconnections between retinal and renal microvascular changes. Hypertension, a major risk factor for renal impairment, also affects retinal microvasculature. This study investigates the relationship between retinal vascular density, assessed by Optical Coherence Tomography Angiography (OCT-A), and early renal dysfunction in hypertensive patients. Methods: A total of 142 hypertensive patients (mean age 47 ± 13 years; 74% male) were enrolled from the Nephrology and Hypertension Unit at the University of Palermo. Retinal vascular density was measured using OCT-A, and renal function was assessed using estimated glomerular filtration rate (eGFR). Clinical and hemodynamic parameters, including 24-h aortic blood pressure, were also analyzed. Results: Patients with eGFR < 60 mL/min/1.73 m2 exhibited significantly lower retinal vascular densities, particularly in the parafoveal region. Superficial parafoveal density was inversely associated with aortic pulse pressure (p = 0.012) and directly correlated with eGFR (p = 0.012). Deep parafoveal density was independently associated with eGFR (p = 0.001). Multiple linear regression confirmed that lower retinal vascular density was significantly linked to reduced renal function, independent of age and blood pressure. Conclusions: Retinal vascular density, particularly in the parafoveal region, is associated with renal function decline in hypertensive patients. These findings suggest that retinal microvascular changes could serve as a non-invasive biomarker for kidney dysfunction, with potential applications in early risk stratification and disease monitoring. Further research is needed to establish causality and clinical utility.